Mejora en el proceso de control de accesos para personal tercerizado en la unidad Minera de San Rafael en Minsur - Silva Alberti Postigo, Carlos Alejandro (2022)
This document details the development of the Access Control System implementation project for outsourced personnel in a Peruvian company dedicated to the exploitation and treatment of minerals, with operations in 4 units in Peru and 2 in Brazil. One of the organizational values of the company is safety, the objective of the project, aligned with this value, was to implement a solution that guarantees safety within the main mining unit of the company, preventing the entry of personnel who do not comply with the requirements established by the company in accordance with the current legal framework. It was possible to have a solution that allowed to standardize, integrate and optimize the process through a centralized and specialized administration, which allowed greater fluidity and above all greater reliability, reducing the security risks to which the company is exposed in addition to reducing work operational. In the development, the PMI project management methodology and its 5 phases were used as a reference: Start, planning, execution, control and closure, the phases had a duration of 25 weeks and the 2Personnel system was implemented, leader in the mining sector in This process. One of the main challenges faced was resistance to change, which was faced with a clear communication strategy. The implementation cost was 282 thousand dollars, and it had a functional team, IT team and a team of specialists in 2Personnel.